The theology of the Chinese Jews, 1000-1850 - Paper, Jordan D; University of Victoria (B.C.). Centre for Studies in Religion and Society (Waterloo, Ontario, Canada : Wilfrid Laurier University Press, 2012)
Traces the history of Jews in China and explores how their theology's focus on love, rather than on the fear of a non-anthropomorphic God, may speak to contemporary liberal Jews.
1 Introduction: The Four Questions -- 2 From Whence They Came to Where They Went -- 3 Life in China: Tenth to Nineteenth Centuries -- 4 Brief History of Buddhism and the Abrahamic Traditions in China -- 5 The Sinification of Judaism -- 6 A Speculative Theology of the Chinese Jews -- Epilogue.
Co-published by: University of Victoria, Centre for Studies in Religion and Society.
Includes bibliographical references (pages 166-170).
Includes an appendix of Chinese logographs for terms and translations in chapter 6.
Print version record.
Master record variable field(s) change: 072
Keywords: Jews -- China -- History; Jews -- China -- Kaifeng Shi -- History; Judaism -- China -- Doctrines; China -- Ethnic relations -- History; HISTORY -- Asia -- China; Ethnic relations; Jews; Judaism -- Doctrines; China; China -- Kaifeng Shi; Electronic books; History